New Approach to Support Region Determination of the µ-law Quantizer - Peric, Z.; Aleksic, D.; Stefanovic, M.; Nikolic, J. (Elektronika ir Elektrotechnika, 2013)
In this paper we address the optimization of the support region threshold of the µ-law companding quantizer designed for the Laplacian source of unit variance. We propose a new iterative method of determining the support region threshold, based on Newton's method. We provide a simple manner for determining the support region threshold. Numerical results show that the proposed new approach to the observed optimization problem outperforms the recently proposed method in terms of the relative error of determining the support region threshold. This indicates the usefulness of the proposed approach. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5406